2022
DOI: 10.3390/horticulturae8070623
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Compounds from Tea Plants (Camellia sinensis (L.) Kuntze) and the Effect of Identified Compounds on Empoasca flavescens Behavior

Abstract: The tea green leafhopper, Empoasca flavescens, is a major pest of tea Camellia sinensis (L.) Kuntze. Until recently, it has mainly been controlled by pesticides, but their use has led to high levels of toxic residues in plants, which threaten both the environment and human health. Therefore, a safer biological control approach is needed. Tea plants produce many volatile compounds, and different tea clones differ in their resistance to the pest. We explored the possibility that volatile compounds influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In recent years, the interaction between tea plants and insects has largely focused on volatile compounds [ 5 , 32 ]. Tea plants usually release a large amount of volatile metabolites, such as terpenoids, green leaf volatiles and other aromatic compounds, in response to attack by invaders such as pathogens and pests [ 5 , 32 , 33 , 34 ]. These induced volatile metabolites may have the function of plant protection and are also important tea-quality components [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the interaction between tea plants and insects has largely focused on volatile compounds [ 5 , 32 ]. Tea plants usually release a large amount of volatile metabolites, such as terpenoids, green leaf volatiles and other aromatic compounds, in response to attack by invaders such as pathogens and pests [ 5 , 32 , 33 , 34 ]. These induced volatile metabolites may have the function of plant protection and are also important tea-quality components [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that styrene could be significantly induced by infection with blister blight disease, while (Z)-3-hexenyl acetate was negatively affected, which was not consistent with previous studies that showed terpenes, azotic, sulfur, aromatic and green leaf volatiles were the main volatiles in blister blight-infected tea leaves [ 17 , 32 ]. A previous study showed that (Z)-3-hexenyl hexanoate and (Z)-3-hexenyl acetate can be elicited in tea plants attacked by tea geometrid ( Ectropis obliqua ) [ 34 ], and styrene is involved in the resistance to tea green leafhopper ( Empoasca flavescens ) [ 33 ]. Some other volatiles, such as (E)-nerolidol, were detected in much lower amounts in our study ( Figure 5 ), and were reported to be a volatile signal that participated in the defense of tea plants against both a herbivore ( Empoasca ) and a pathogen ( C. fructicola ) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…With PCA, we can reduce the dimension of the VOC profiles to a linear combination of variables (principal components) and also group genotypes based on the studied traits [39,40,46,47]. The technique has a wide domain of applications including use in VOC studies [39,40,[46][47][48][49]. The output of the analysis is expressed in terms of principal components (PC), their % variance, and loading of the variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…There is evidence that different plant cultivars of given crop species might produce different suites of volatiles [20,39,41,47,48]. The inherent variability of constitutive VOC emissions among plant genotypes has been studied and differences in specific VOC abundance between resistant and susceptible genotypes has been observed [24,40].…”
Section: Quantitative and Qualitative Differences In Constitutive Voc...mentioning
confidence: 99%
“…Usually, pest control involves many chemical pesticides, which may contaminate land and water resources and then cause a series of environmental problems. In addition, the use of the pesticide over a long period causes pest resistance and reduces the effectiveness of pest elimination [1][2][3][4][5]. Therefore, it is necessary to explore new methods for pest management without contamination emission and pest resistance.…”
Section: Introductionmentioning
confidence: 99%